THE ATTEMPTS TO IMPROVE THE FORMAL TRANSPORT SYSTEM IN THE KINGDOM OF POLAND DURING THE CRISIS IN THE EARLY 1860S - Marek RUTKOWSKI (Scientific Journal of Silesian University of Technology. Series Transport)
The purpose of this paper is to focus on the possibilities for improving the administration and delivery of the Polish transport system, which occurred in early 1860s, the last phase of local autonomous government.